An Overview of Systemic Entrepreneurship - Paul Jones (Systemic Entrepreneurship: Contemporary Issues and Case Studies, 2015)
Finding answers for renewed socioeconomic growth in the current global landscape seems to be a daunting task. Although a plethora of entrepreneurial development initiatives exist results seems not to be forthcoming. Rethinking the way entrepreneurship is promoted is therefore called for and the focus of this drive is systemic entrepreneurship. Through systemic entrepreneurship a broader holistic and heuristic approach can be achieved leading to improved policy formulation promoting socioeconomic growth. Within this chapter systemic entrepreneurship is discussed and supported by input on the role of business schools supporting systemic entrepreneurship. The chapter concludes underlining the fact that systemic entrepreneurship is a multi-disciplinary and multifaceted approach to the current and future challenges faced worldwide.